Do German Works Councils Counter or Foster the Implementation of Digital Technologies? - Sabrina Genz; Lutz Bellmann; Britta Matthes (Institute of Labor Economics (IZA), 2018)
As works councils' information, consultation and co-determination rights affect the decision process of the management, works councils play a key role in the implementation of digital technologies in establishments. However, previous research focuses on the potential of digital technologies to sub-stitute for labor and its impact on labor market outcomes of workers. This paper adds the role of industrial relations to existing literature by analyzing the impact of works councils on the implementation of digital technologies. Theoretically, the role of works councils in the digital transformation is ambiguous. Using establishment data from the IAB Establishment Survey of 2016 combined with individual employee data from the Federal Employment Agency and occupational level data about the physical job exposure, empirical evidence indicates an ambivalent position of works councils to-wards digital technologies. The sole existence of works councils leads to statistically significant lower equipment levels with digital technologies. However, works councils foster the equipment with digital technologies in those establishments, which employ a high share of workers who are conducting physical demanding job activities. Thus, this study highlights the importance of establishment-level workforce representation for the digital adoption process within Germany.
Keywords: J50; J53; 330; co-determination; digital technologies; works councils; industrial relations; entropy balancing